Identity lost and found: Lessons from the sixties scoop - Sinclair, Raven (First Peoples Child & Family Review, 2007)
The “Sixties Scoop” describes a period in Aboriginal history in Canada in which thousands of Aboriginal children were removed from birth families and placed in non-Aboriginal environments. Despite literature that indicates adoption breakdown rates of 85-95%, recent research with adults adopted as children indicates that some adoptees have found solace through reacculturating to their birth culture and contextualizing their adoptions within colonial history. This article explores the history of Aboriginal adoption in Canada and examines some of the issues of transracial adoption through the lens of psychology theories to aid understanding of identity conﬂicts facing Aboriginal adoptees. The article concludes with recommendations towards a paradigm shift in adoption policy as it pertains to Aboriginal children.